2021
DOI: 10.3390/rs13132627
|View full text |Cite
|
Sign up to set email alerts
|

Towards Amazon Forest Restoration: Automatic Detection of Species from UAV Imagery

Abstract: Precise assessments of forest species’ composition help analyze biodiversity patterns, estimate wood stocks, and improve carbon stock estimates. Therefore, the objective of this work was to evaluate the use of high-resolution images obtained from Unmanned Aerial Vehicle (UAV) for the identification of forest species in areas of forest regeneration in the Amazon. For this purpose, convolutional neural networks (CNN) were trained using the Keras–Tensorflow package with the faster_rcnn_inception_v2_pets model. Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 57 publications
1
16
0
1
Order By: Relevance
“…Like Ferreira et al [28] and Moura et al [29], this study demonstrates that RPA has high potential to map relevant species in the Amazon biome automatically. Besides mapping species, this study also showed that low-cost RPA is capable of automatic mapping and delineating individual crowns of all kinds of trees in a tropical high diverse forest.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Like Ferreira et al [28] and Moura et al [29], this study demonstrates that RPA has high potential to map relevant species in the Amazon biome automatically. Besides mapping species, this study also showed that low-cost RPA is capable of automatic mapping and delineating individual crowns of all kinds of trees in a tropical high diverse forest.…”
Section: Discussionsupporting
confidence: 67%
“…In other studies on Cecropia, Wagner et al [68] accurately identified Cecropia hololeuca using deep learning (U-Net algorithm, which performs semantic segmentation) applied on a satellite image of the Brazilian Atlantic Forest biome. Moura et al [29] accurately mapped Cecropia using faster_R-CNN_inception_v2_pets model on an RPA image, which generates a bounding box in its results. In this work, each Cecropia crown was delineated in an instance segmentation process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These limitations, with some exceptions, such as the United States, England, and other European countries, where good-quality and open LiDAR data are more easily available [74], have been addressed by the scientific community and forest managers, who have found in UAV flights a solution to the acquisition of quality LiDAR data, even with the limitation of geographic scale, representing an advance in the use of this technology in urban forestry science [81,82]. The versatility and reasonable cost of LiDAR data acquired from UAV has allowed for a more abundant use of this data source in forestry research [61]. Although many of the studies analyzed conclude that LiDAR data work well as auxiliary information, Degerickx et al [83] and Wang et al [73] found that LIDAR data could play a central role in the characterization of urban trees, as it provides the most important information for structural, and textural features of trees.…”
Section: Lidarmentioning
confidence: 99%
“…In turn, more sophisticated algorithms, such as clustering and segmentation methods [48,56], integrated into geographical information systems (GIS), have facilitated the analysis of large-scale remotely sensed data. Computational developments during the last decades brought novel artificial intelligence (AI) techniques, which tap into the ability of computers to mimic human reasoning [57], solving complex problems such as object classification and damage assessment [58][59][60][61][62]. These advances are especially recent in the field of machine learning (ML) [63], where algorithms, such as random forest (RF) and support vector machine (SVM), and more recently, neural network-based deep learning (DL), algorithms have been developed [48,59], improving classification problems, such as individual tree characterization.…”
Section: Introductionmentioning
confidence: 99%